Methods for the thawing time prediction of ellipses - Ilicali, Coskan (Academic Press, 1997)
Methods for predicting the thawing times of ellipses are proposed. A finite difference numerical model was used for numerical data generation. The thawing time predictions of the methods were compared with numerical results. With the analytical methods considered, it was possible to predict the numerical results with errors lower than 5.4%.